9r2-4s2/9r+6s
It looks like you can factors the numerator
(3r + 2s)(3r - 2s) [This is the factored form of 9r2-4s2]
Put this back into the equation
(3r+2s)(3r-2s)/9r+6s
You can also factor the denominator
3(3r+2s)
Put this back into the equation
(3r+2s)(3r-2s)/3(3r+2s)
You can cancel out the 3r+2s on top and bottom because they are the same they equal 1. Therefore your final answer is
3r-2s over 3
You could go further and say this is...
r-(2/3)s
either one is correct
Chat with our AI personalities
13s - 2
s + 3 = 6s -s -s ------------- 3 = 5s /5 /5 s=3/5 or s=.6
-40 = 8-6s -40 - 8 = 6s -48 = 6s 8 = s
9s+6s-12s=24... Ignore the 's' for a moment giving the sum 9+6-12=24 - This results in the answer 3 x 'something' = 24. Therefore s=8 !
6s, 12s, 18s, 24s, 30s, 36s and so on.